2021
DOI: 10.35691/jbm.1202.0206
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Biodegradation through Insects and their Symbionts Microbes: A Review

Abstract: Plastic waste has recently been identified as one of the most serious environmental issues, affecting all life forms, natural habitats, and the economy, and is one of the most serious global environmental problems, second only to climate change. Seeking alternative environmentally sustainable options, such as biodegradation instead of conventional disposal, is critical in the face of this challenge. However, there is currently a lack of information about the mechanisms and efficacy of plastic biodegradation. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Insect-associated gut microbes have been studied for their bioremediation ability using contaminants, pollutants, and toxins as nutritional sources ( Loredo-Treviño et al, 2012 ; Banerjee et al, 2021 ). Insects and their gut microbes have gained attention as promising resources for plastic biodegradation ( Bilal et al, 2021 ). Recent studies have reported that bacterial strains from Tenebrio molitor ( Yang et al, 2015 ) and Triboluim castaneum ( Wang et al, 2020 ) efficiently degrade polystyrene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insect-associated gut microbes have been studied for their bioremediation ability using contaminants, pollutants, and toxins as nutritional sources ( Loredo-Treviño et al, 2012 ; Banerjee et al, 2021 ). Insects and their gut microbes have gained attention as promising resources for plastic biodegradation ( Bilal et al, 2021 ). Recent studies have reported that bacterial strains from Tenebrio molitor ( Yang et al, 2015 ) and Triboluim castaneum ( Wang et al, 2020 ) efficiently degrade polystyrene.…”
Section: Discussionmentioning
confidence: 99%
“…Plastics are composed of chains comprising numerous organic subunit linked by dynamic covalent bonds and are widely used owing to their stability, ease of manufacturing, economic efficiency, and convenience (Alabi et al, 2019;Atanasova et al, 2021;Roy et al, 2021). Plastic production has grown exponentially, with a very large number of plastics produced since 1950 (Bilal et al, 2021). Plastic disposal systems, such as incineration, recycling, and landfills, are ineffective in plastic waste management (Seneviratne et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Biodeterioration is a quasi-abiotic step, where tandem weathering processes, including extreme temperatures, mechanical work, abiotic hydrolysis, and photooxidation cause surface imperfections in the plastic, resulting in an increase in bioavailable surface area. Once the polymer matrix is compromised, biofragmentation ensues as macro-organisms (e.g., nematodes, earthworms, and snails) and microorganisms (e.g., bacteria, fungi, algae, and protozoa) colonize the polymer surface and employ microbial gut symbionts or secreted enzymes to cleave accessible macromolecular chains into shorter oligomers and monomers [15]. These smaller molecules are then digested by macro-organisms or are assimilated and/or mineralized by cells.…”
Section: Introductionmentioning
confidence: 99%
“…The various reports of biodegradable microbes are from dumping ground, open ocean, seashore, and leftovers from oil refineries due to their property to provide an optimum condition for the microbe to grow and evolve against the high concentration of plastic waste (Amobonye et al ., 2021; Emadian et al ., 2017; Lebreton et al ., 2018; Zhao et al ., 2021). Recent reports of mealworm-based plastic assimilation and the role of gut microbiota are pointing toward a large-scale worm-based solution of plastic waste (Yang et al ., 2020; Kundungal et al ., 2019; Kim et al ., 2020; Bilal et al ., 2021). On the other hand, the known biocatalysts that degrade similar linker bonds in biopolymers such as amidase, hydrolase, and esterase were also found to be effective degraders of C-X group’s plastic types.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the continued availability of plastic in the open environment, weathering causes fragmentation of plastic material into microplastic, which exacerbates the problem (Verla et al, 2019) and have become a hotspot for antibiotic-resistant microorganisms to form biofilms (Kirstein et al, 2018;Dussud et al, 2018;Jacquin et al, 2019), revealing a wide range of antibiotic resistance genes of pathogenic bacteria growing on microplastics (Jacquin et al, 2019). There are reports of contamination in every level of the food chain, including human beings (Cox et Bilal et al, 2021). On the other hand, the known biocatalysts that degrade similar linker bonds in biopolymers such as amidase, hydrolase, and esterase were also found to be effective degraders of C-X group's plastic types.…”
Section: Introductionmentioning
confidence: 99%